Macroprudential policy frameworks in developing Asian economies - Minsoo Lee; Raymond Gaspar; Mai Lin C. Villaruel (Asian Development Bank (ADB), 2017)
Over the last decade, developing Asia's deeper global financial linkages have been accompanied by greater financial integration. As the region becomes more interconnected, a key priority is to ensure that the dynamic environment is supported by better coordinated and potentially consistent macroprudential policies to adequately control systemic risks. Within the context of global financial developments, this paper presents a general macroprudential policy framework that highlights important aspects to conducting policy. It also provides an overview of how some Asian economies, New Zealand, and the euro area implement their macroprudential policies. It reviews existing macroprudential policy frameworks of five high-growth developing economies - Cambodia, Mongolia, Myanmar, Sri Lanka, and Viet Nam - identifying improvements and continuing challenges for their financial systems, which will likely grow more complex. Identifying and addressing key issues will help improve their existing macroprudential policy frameworks.
Keywords: G01; G28; L51; 330; developing Asia; financial stability; macroprudential framework; systemic risk